All That Glitter is not Gold: Computed Tomography-Kidney Ureter Bladder (CT-KUB) is not necessary for a Safe Percutaneous Nephrolithotomy - Dr Hamza Ashraf; Dr Sherjeel Saulat; Dr Syed Saeed uddin Qadri; Dr Dur Amin; Dr Awais Ayub; Dr Numan sadiq kiani; Dr Mansoor Ejaz (ziauddin University, 2024)
Background:  Diagnosis of renal stones is tricky and appropriate diagnosis requires exact location and size identification of renal stones along with the degree of obstruction and hydronephrosis. This study aimed to compare the difference between Ultrasound and Computed tomography Kidney ureter Bladder (CT KUB) groups for stone clearance, diagnostic accuracy, laboratory parameters, and complications. Methods: This is a cross-sectional, comparative effectiveness trial; patients (n=100) with suspected renal stones were randomly assigned with a 1:1 ratio in two different imaging groups, Group A (n=50) participants had ultrasonography and group B (n=50) patients had Computed tomography as a diagnostic imaging modality. The complications and operative differences were compared with the help of student t-test and chi-square tests, a p-value of 0.05 was considered statistically significant. Results: The mean age of the patients was 37.3 ± 17 years and 45.8 ± 14.7 years in group A and group B, respectively. The study found no difference (0.3 and 0.1) between pre-operative stone size measurements of the renal unit by ultrasound and CT [(2.4±0.9 cm and 2.7±1.8cm (right) 1.8±1.0 cm and 1.9±0.7 cm (left)]. The sensitivity and specificity of USG for renal stone diagnosis was 84.8%, while CT indicated 86% accuracy, X-Ray KUB was used for radiopaque stones only and showed 78.6% sensitivity and specificity. Conclusion: The pre-operative stone sizes indicated in ultrasonography and CT were similar in intra-operative, retrograde pyelogram (RPG) measurements, referred to the accuracy of stone size prediction. Simple x-ray and ultrasonography are cost-effective, easily available in hospitals, with minimal radiation exposure. Keywords: Percutaneous Nephrolithotomy; Ultrasonography; Kidney Stones.